Characteristics of Carbonated Teter Leaf Loloh (Solanum erianthum D.Don) with Lemon and Red Ginger Flavor as a Functional Beverage - Ery, Ni Kadek; Putra, I Gede Arie Mahendra; Kenari, Ni Ketut Ratnamaya Sutra; Putri, Safa Reska; Sutisna, Arlin Ramadhan (Pro Food, 2025)
Loloh is a traditional Balinese herbal drink made from a mixture of several herbs. One of which is loloh teter leaves from Taro Village, Gianyar. Its bitter taste and unappealing aroma make it less preferred by consumers. An innovation was carried out by adding lemon and ginger flavors to improve its taste and overall acceptability. This research aimed to evaluate the effect of flavor addition on the sensory characteristics of loloh teter leaf and determine the most suitable flavor to enhance its sensory attributes. The research employed a Completely Randomized Design with treatments included: control (untreated) loloh teter leaf, carbonated loloh teter leaf (without added flavor), carbonated loloh teter leaf flavored with 5% lemon, carbonated loloh teter leaf flavored with 5% red ginger, and carbonated loloh teter leaf flavored with a combination of 2.5% red ginger and 2.5% lemon. The variables observed were sensory characteristics (color, taste, aroma, and overall acceptance). The best treatment was further analyzed for color, pH, total soluble solids, total phenolics, and antioxidant activity. The results showed that the best sensory characteristics were obtained from carbonated loloh teter leaf with a combination of 2.5% red ginger and 2.5% lemon flavor. This combination had moderate ratings for color and aroma, slightly preferred taste, and slightly preferred overall acceptance. The color characteristics were L* 37.3, a* -4.5, b* 22.0, pH 6, total soluble solids 13.3, total phenol 2.51 mg/100g, and antioxidant activity of 42.14%, thus has potential to be developed as a functional beverage.